Influences of evergreen gymnosperm and deciduous angiosperm tree species on the functioning of temperate and boreal forests. (11th June 2014) - Augusto, Laurent; De Schrijver, An; Vesterdal, Lars; Smolander, Aino; Prescott, Cindy; Ranger, Jacques
ABSTRACT It has been recognized for a long time that the overstorey composition of a forest partly determines its biological and physical–chemical functioning. Here, we review evidence of the influence of evergreen gymnosperm (EG) tree species and deciduous angiosperm (DA) tree species on the water balance, physical–chemical soil properties and biogeochemical cycling of carbon and nutrients. We used scientific publications based on experimental designs where all species grew on the same parent material and initial soil, and were similar in stage of stand development, former land use and current management. We present the current state of the art, define knowledge gaps, and briefly discuss how selection of tree species can be used to mitigate pollution or enhance accumulation of stable organic carbon in the soil. The presence of EGs generally induces a lower rate of precipitation input into the soil than DAs, resulting in drier soil conditions and lower water discharge. Soil temperature is generally not different, or slightly lower, under an EG canopy compared to a DA canopy. Chemical properties, such as soil pH, can also be significantly modified by taxonomic groups of tree species. Biomass production is usually similar or lower in DA stands than in stands of EGs. Aboveground production of dead organic matter appears to be of the same order of magnitude between tree species groups growing on the same site. Some DAs induce more rapid decomposition of litter than EGs because of the chemical properties of their tissues, higher soil moisture and favourable conditions for earthworms. Forest floors consequently tend to be thicker in EG forests compared to DA forests. Many factors, such as litter lignin content, influence litter decomposition and it is difficult to identify specific litter‐quality parameters that distinguish litter decomposition rates of EGs from DAs. Although it has been suggested that DAs can result in higher accumulation of soil carbon stocks, evidence from field studies does not show any obvious trend. Further research is required to clarify if accumulation of carbon in soils (i.e. forest floor + mineral soil) is different between the two types of trees. Production of belowground dead organic matter appears to be of similar magnitude in DA and EG forests, and root decomposition rate lower under EGs than DAs. However there are some discrepancies and still are insufficient data about belowground pools and processes that require further research. Relatively larger amounts of nutrients enter the soil–plant biogeochemical cycle under the influence of EGs than DAs, but recycling of nutrients appears to be slightly enhanced by DAs. Understanding the mechanisms underlying forest ecosystem functioning is essential to predicting the consequences of the expected tree species migration under global change. This knowledge can also be used as a mitigation tool regarding carbon sequestration or management of surface waters because the type of tree species affects forest growth, carbon, water and nutrient cycling.